The Effect of Dual-Species Biofilms, Monosaccharide and D-Amino Acids on Pseudomonal Biofilm - Al-Moghira Khairi Al-Qaysi1 ; Safaa Abed Latef Al-Meani2 ; Mushtak T.S. Al-Ouqaili3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The major therapeutic failure in clinical settings is due to problematic biofilm-producingbacteria like Pseudomonas aeruginosa. This study aims to investigate the effect of dual-species biofilms,monosaccharide, and D-amino acids on pseudomonal biofilm. Methodology: A total of 130 patients withcatheter-associated urinary tract and wound infections were involved in this study. Quantitative biofilmassay by alginate beads was performed. The dual-species biofilms have been done, and the effect ofciprofloxacin, monosaccharides, and D-amino acids on sessile cells was detected. Conclusion: This studysuggested that the combined action of both monosaccharides (glucose and galactose) and the combination ofeach one with ciprofloxacin is the enhancing of P. aeruginosa biofilm and increases survival strategy againstciprofloxacin. In contrast, a noticeable biofilm reduction and marked synergistic action for ciprofloxacinhave been determined in the combination of the two D-amino acid, alanine, and glycine in comparison tothe effect of each one alone. Furthermore, the dual biofilm of P. aeruginosa with each of K. pneumonia andE. coli, markedly reduced pseudomonal biofilm, while co-culture with S. aureus revealed strong support ofpseudomonal pathogenicity and increased its biofilm production.